An evaluation of Qol-Steps : idiographic assessment of quality of life for patients in palliative care : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Jardine, Andrew (Massey University, 1999)
The primary objective of this study was to evaluate an assessment tool that would enable patients in palliative care to communicate their individual quality of life(QoL) concerns. An examination of existing QoL assessment instruments suggested that most were based upon assumptions more appropriate for research on groups of patients. Such assessment can be classified as standard needs measures. While useful for comparing patients at the aggregate level, standard needs approaches to assessing QoL may not be useful in clinical situations. Instead, an idiographic approach to the assessment of QoL was adopted and it is the development of a particular instrument, called QoL-Steps, which forms the basis for this study. QoL-Steps used a graphical procedure that enabled patients to nominate their important personal aspects of quality of life, rank these aspects in order of importance, and rate the current and ideal levels of each aspect in two different time periods. The data from a sample of 42 out-patients of a hospice programme, highlighted the variability that would be expected from an idiographic approach to the assessment of individual patients. Results from Qol-Steps suggest that the instrument is a viable tool. QoL-Steps provided a wide range of variability for patients, in terms of content, difference scores, rankings and patterns of change. Importantly, many patients saw QoL-Steps as a means of communicating their unique needs within an individual context.
Keywords: Palliative treatment; Psychology; Quality of life; Terminally ill